Overlooked and undervalued: The neglected role of fauna and a global bias in ecological restoration assessments - Cross, Sophie; Tomlinson, Sean; Craig, M.D.; Dixon, Kingsley; Bateman, Bill (2019)
Globally increasing rates of mine site discontinuations are resulting in the need for immediate implementation of effective conservation and management strategies. Surveying vegetation structure is a common method of assessing restoration success; however, responses of fauna to mine site restoration remain largely overlooked and understudied despite their importance within ecosystems as ecological engineers, pollinators, and restoration facilitators. Here we review the current state of the use of fauna in assessments of mine site restoration success globally, and address biases or shortcomings that indicate the assessment approach may undershoot closure and restoration success. We identified just 101 peer-reviewed publications or book chapters over a 49-year period that assess responses of fauna to mine site restoration globally. Most studies originate in Australia, with an emphasis on just one company. Assessments favour general species diversity and richness, with a particular focus on invertebrate responses to mine site restoration. Noteworthy issues included biases towards origin of study, study type, and target taxa. Further searches of the grey literature relating to fauna monitoring in mine site restoration, which was far more difficult to access, yielded six monitoring/guidance documents, three conference proceedings, two book chapters without empirical data, and a bulletin. As with peer-reviewed publications, grey literature focussed on invertebrate responses to restoration, or mentioned fauna only at the most basic level. We emphasise the need for global re-evaluation of regulatory standards to address these major limitations in assessing the capacity of the mining industry to comprehensively and representatively restore faunal communities after mining.